An Elective Course on Pharmacy-Based Health Screenings - Raney, Erin C. (American Journal of Pharmaceutical Education, 2013)
Objective. To provide an elective course for pharmacy students focused on the knowledge and skills necessary to implement health screenings in a pharmacy environment. Design. Course lectures focused on expert recommendations for health screenings as well as regulatory requirements and procedures integral to the implementation of screening services. Workshops provided hands-on experience with blood glucose, body composition, bone density, and cholesterol testing devices. Assessment. Attainment of knowledge and skills was assessed by patient case assignments, screening device demonstrations, group projects, and a final quiz. Annual course evaluations revealed consistently favorable student feedback regarding the course design and content. Students reported a high level of preparedness and interest in participating in health screening services in future practice. Conclusion. An elective course focused on the delivery of health screenings in pharmacy settings was well received by student participants and exposed students to a unique opportunity in patient care.